REALITAS KOMUNIKASI KELUARGA PEDAGANG: SEBUAH PENDEKATAN FENOMENOLOGIS - Muftitama, Adriansyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research explores the influence of parental social construction on family orientation in merchant families. The study, which used a phenomenological qualitative approach, focused on merchant families in Jambi City who have experienced household problems. The research findings highlight several key aspects of family orientation. Firstly, family climate significantly affects the relationships between family members. Secondly, materialistic orientation places a strong emphasis on financial success. Thirdly, independent and resilient orientation is shaped by the parents in merchant families. Lastly, spirituality strongly influences religious values within the family. The study also explains how the social construction of family climate, upbringing, and language shape the materialistic, self-reliant, and spiritual orientations of merchant families, ultimately impacting their views and goals. Overall, this research sheds light on the important role of parents in shaping the social order within the family and their influence on various aspects of family orientation in merchant families.